Influence of blood pressure and calcineurin inhibitors on kidney function after heart or liver transplantation - Morath, Christian; Opelz, Gerhard; Döhler, Bernd; Zeier, Martin; Süsal, Caner (Transplantation, 2018)
Chronic kidney disease is common after heart or liver transplantation, with calcineurin inhibitors (CNI) considered the key contributor. A possible influence of posttransplant blood pressure has not been extensively examined. Data from adult recipients of a first heart or liver transplant were analyzed regarding the relationship between blood pressure at year 1, renal function at year 5, and CNI therapy. Although we confirmed the well-known detrimental effect of increased 1-year systolic blood pressure on 5-year kidney graft survival, heart or liver graft survival was not affected. However, among 2534 heart transplant recipients with good renal function at year 1, increasing systolic blood pressure at year 1 was associated with higher rates of poor renal function at year 5 posttransplant. This association was confirmed on multivariate analysis overall (odds ratio, 1.25 per 20 mm Hg increment; P < 0.001) and within subgroups. Similar results were observed in 1822 liver transplant recipients (odds ratio, 1.35; P < 0.001). Neither the type of CNI nor CNI dose or trough level at year 1 showed a significant association with kidney function at year 5. One-year blood pressure was identified as the major modifiable risk factor associated with deteriorating kidney function between years 1 and 5 after heart or liver transplantation.